Mare’s Milk Productivity of Different Breeds - Kalimbetov Bakhadir Salauat ugli (Universitas Muhammadiyah Sidoarjo, 2022)
In the Republic of Uzbekistan, camel and horse breeding are mainly practiced in the northern Kyzylkum regions of the Republic of Karakalpakstan. In the Republic of Karakalpakstan, the total number of annuals in all kinds of farms is currently 7070. Improving horse productivity and making full use of their genetic potential, creating productive lines, and developing effective strategies to promote output are all crucial.